#### Answer

2

#### Work Step by Step

Using order of operations, first solve numerator and denominator separately, then simplify the fraction.
$\frac{-3 - 5^{2}}{2(-7)} = \frac{-3 - 25}{2(-7)} = \frac{-28}{2(-7)} = \frac{-28}{-14} = 2$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

2

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.